Application of Anthracite and Activated Carbon Filter Media to Enhance Injection Water Quality for Water Flooding Operations in “DE” Field - Effendi, Dahrul; Rohmana, Rian Cahya; Setiyaningrum, Priskila Rully; Muhamad Bisyir, Aliyah (Testing Center for Oil and Gas LEMIGAS, 2025)
Produced water is used as injection water for water flooding. When untreated injection water of poor quality is introduced into the formation, it can lead to severe plugging issues. This is primarily due to the poor quality of the water, which is characterized by high levels of solid particles, elevated turbidity, a high scaling index, significant oil content, high TSS concentration, and a high RPI. The application of anthracite and activated carbon filter media has been shown to effectively reduced the scaling index, oil content, turbidity, particle size, TSS, and RPI in the injection water. These filter media enable the filtering out of insoluble materials from the injection water. By evaluating the effectiveness of different filter media on injection water quality, it is possible to select a filtrate with improved water quality, characterized by a clear appearance and minimal amounts of solid particles. The resulting filtrate demonstrated very low TSS concentrations and a significantly reduced RPI value. Overall, the filtrate can be classified as high-quality injection water suitable for water-flooding applications. The morphology of TSS before and after filtration through anthracite and activated carbon filter media was detected using SEM.